Writing research proposals & theses : substance, structure and style - Moten, Abdul Rashid (Prentice Hall, 2009)
This book provides expert advice to master's and doctoral degree students on the entire dissertation process from selectiong a suitable topic for research to writing and presenting the thesis in an acceptable format. It shows that the scientific method applied in the West is rooted in Islam and was used by Muslim scholars. It shuns the dichotomy between quantitative and qualitative approaches to research and argues that both the methods are required in social and political research and that the two approaches can usefully be treated together. It is organised according to the stages of research-and-writing process.